(untitled) (Global Journal of Management and Business Research, 2021)
Student housing plays an important role in achieving of high-quality education Significant evidence of the inadequacy of these important facilities among public universities in Nigeria have been provided It was further noted that there is a lack of adequate information within the private institutions in the country with regards to this situation Based on this context this study was carried out to evaluate the housing situation of students at the University of Ibadan by evaluating the factors influencing the choice of residence of students and their effect on their academic performance However the study adopted a survey approach with 200 students sampled through a structured questionnaire Data gathered were analyzed using frequency mean item score and ANOVA test Results revealed that although gender has no relationship with students choice of residence but age and academic level does This implies that the older the students get and the higher they go on the academic ladder the greater the propensity to stay off- campus